Antibacterial Activity of Endophytic Bacteria Against Sugar Beet Root Rot Agent by Volatile Organic Compound Production and Induction of Systemic Resistance - Safara, Somayeh; Harighi, Behrouz; Bahramnejad, Bahman; Ahmadi, Slahadin (Frontiers in Microbiology, 2022)
The volatile organic compounds (VOCs) produced by endophytic bacteria have a significant role in the control of phytopathogens. In this research, the VOCs produced by the endophytic bacteria Streptomyces sp. B86, Pantoea sp. Dez632, Pseudomonas sp. Bt851, and Stenotrophomonas sp. Sh622 isolated from healthy sugar beet (Beta vulgaris) and sea beet (Beta maritima) were evaluated for their effects on the virulence traits of Bacillus pumilus Isf19, the causal agent of harvested sugar beet root rot disease. The gas chromatography-mass spectrometry (GC-MS) analysis revealed that B86, Dez632, Bt851, and Sh622 produced 15, 28, 30, and 20 VOCs, respectively with high quality. All antagonistic endophytic bacteria produced VOCs that significantly reduced soft root symptoms and inhibited the growth of B. pumilus Isf19 at different levels. The VOCs produced by endophytic bacteria significantly reduced swarming, swimming, and twitching motility by B. pumilus Isf19, which are important to pathogenicity. Our results revealed that VOCs produced by Sh622 and Bt851 significantly reduced attachment of B. pumilus Isf19 cells to sugar beet roots, also all endophytic bacteria tested significantly reduced chemotaxis motility of the pathogen towards root extract. The VOCs produced by Dez632 and Bt851 significantly up-regulated the expression levels of defense genes related to soft rot resistance. Induction of PR1 and NBS-LRR2 genes in sugar beet root slices suggest the involvement of SA and JA pathways, respectively in the induction of resistance against pathogen attack. Based on our results, the antibacterial VOCs produced by endophytic bacteria investigated in the current study can reduce soft rot incidence.